Introducing SDL Trados to Beginning Translators - Lemmuela Alvita Kurniawati; Dian Titi Rahajeng; Barlian Kristianto; Fidelis Chosa Kastuhandani (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2016)
Over years, translators have been incorporating new advances in technology into their work. A number of attempts in developing ideal translator’s workstations using technology have been made, one of such stations is a Computer-Aided Translation (CAT) tool. CAT tools facilitate translators to increase their productivity and efficiency by providing them with some utilities, such as a Translation Memory and an Alignment Tool to support their translation works. This article highlights the usefulness of SDL Trados 2014, as one of the most widely used paid CAT tools, in translating the texts more effectively and in a timely manner. Further, it describes the basic steps in using SDL Trados and exemplifies SDL Trados 2014 translation results. A sample text was translated from Indonesian to English using both Across (a free CAT tool) and SDL Trados (a paid CAT tool). Eventually, the results of translating using both CAT tools appear to prove that SDL Trados helps the translators to translate more consistently, accurately, effectively and in a timely-manner.